Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I'm supopsed to show that if $m$ and $n$ are non-negative integers then

$$\sum_{k=0}^{n}(-1)^k {{m+1}\choose{k}}{{m+n-k}\choose{m}} = \left\{ \begin{array}{l l} 1 & \quad \text{if $n=0$}\\ 0 & \quad \text{if $n>0$} \end{array} \right.$$

I used mathematical induction about $n$, but I couldn't reach at the answer. Also, I tend to make the process to show this type of equality quite non-elegant, so I want a concise solution for this. Since the case of $n=0$ was already proved, you don't need to show it.

share|cite|improve this question
    
Have you tried a combinatoric proof using the inclusion/exclusion principle ? – Lucian May 31 '14 at 9:34
up vote 2 down vote accepted

We may use convolution of generating functions:

Let \begin{align*} a_k &= (-1)^k\, \binom{m+1}{k} \\ b_k &= \binom{m+k}{m} \end{align*}

The corresponding g.fs are: \begin{align*} A(x) &= (1-x)^{m+1} \\ B(x) &= \frac{1}{(1-x)^{m+1}} \end{align*} Multiplying $A(x)$ and $B(x)$ \begin{align*} A(x)\cdot B(x) &= \sum_{n\ge 0} \left(\sum_{k=0}^{n} a_k\, b_{n-k}\right) x^n \\ &= \frac{(1-x)^{m+1}}{(1-x)^{m+1}} \\ &= 1 \end{align*}

which verifies that the sum is $1$ only when $n=0$

share|cite|improve this answer
    
Thanks! I especially wanted to know a proof using generating function like this one. – Math.StackExchange Jun 1 '14 at 22:02
    
You are welcome! – gar Jun 2 '14 at 3:20

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.